OP0055 MINIMAL RADIOGRAPHIC DAMAGE OF SACROILIAC JOINTS DETECTED IN PSORIATIC ARTHRITIS PATIENTS. (2nd June 2020) - De Hooge, M.; Ishchenko, A.; Steinfeld, S.; Nzeusseu Toukap, A.; Elewaut, D.; Leroi, H.; Lories, R.; De Vlam, K.; Van den Bosch, F.
Abstract : Background: Psoriatic arthritis (PsA) is an inflammatory joint disease that is traditionally included in the Spondyloarthritis (SpA) spectrum. Prevalence and impact of axial involvement in PsA remains understudied but increasingly affects treatment decisions. Objectives: The first step, in this multi-purpose radiographic study, is to report on baseline radiographic damage of the sacroiliac joints (SIJ) in PsA patients from a prospective multicentre cohort study in private and academic rheumatology practices. Methods: Data from the Belgian Epidemiological Psoriatic Arthritis Study (BEPAS), a prospective multicentre cohort involving 17 Belgian rheumatology practices. Recruitment was from December 2012 until July 2014. Patients were included in the study when the local rheumatologist could diagnose an existing or new PsA and when patients fulfilled the Classification criteria for Psoriatic Arthritis (CASPAR). Radiographs of the SIJ were obtained at baseline and after 2 years. Two calibrated readers assessed radiographic damage by grading the SIJ according to the modified New York (mNY) criteria. When assessing the images, readers were blinded for clinical data and information from other obtained images (radiographs of the hands, feet and spine). Individual scores as well as consensus scores are described. Results: In total 461 patients where included in BEPAS. Mean age was 52.79±12.29 years and 43.0% (n=198) were female; average disease duration was 8.5 ± 9.3 yrs and approximately 34% of the patients report inflammatory axial pain. From 338 patients SIJ radiographs were obtained. At baseline, the vast majority of patients did not fulfil the mNY criteria (n=325, 96.2%), according to both readers. In 8 cases (2.4%) there was concordance on fulfilment of the mNY criteria. Discordant cases (n=5, 1.4%) were equally distributed. Agreement between the 2 readers was good with 98.5% overall agreement and kappa=0.75. Therefore, with a more sensitive approach (any of the 2 readers scores mNY positive) we see slight differences; 13 patients (3.8%) fulfil the mNY criteria. Table 1 shows radiographic damage by individual readers In 128 patients (37.9%) a follow-up x-ray after 2 years was available. In 124 patients (96.9%) there was reader agreement on mNY negative status. There was disagreement between readers on a positive mNY in 2 patients (equally distributed) and agreement on 2 patients (1.6%). There were no patients with consensus between readers on the change in mNY over 2 years, but 1 reader reported 1 patient becoming mNY positive after 2 years. Conclusion: Despite the patient self-identified presence of axial disease in up to 34% in this cohort of PsA patients, there was minimal radiographic damage on SIJ, suggesting that SIJ disease is not a major manifestation of PsA. Disclosure of Interests: Manouk de Hooge: None declared, Alla Ishchenko: None declared, Serge Steinfeld: None declared, Adrien Nzeusseu Toukap Grant/research support from: AbbVie, Celgene Corporation, Janssen, Pfizer, UCB – grant/research support, Consultant of: AbbVie, Eli Lilly, Janssen, Novartis, UCB – consultant, Speakers bureau: AbbVie, Eli Lilly, Janssen, Novartis, UCB – advisory board member, Dirk Elewaut: None declared, Hermine Leroi Employee of: MSD Belgium, Rik Lories Grant/research support from: AbbVie, Boehringer Ingelheim, Celgene Corporation, Eli Lilly, Galapagos, Janssen, MSD, Novartis, Pfizer, Samumed and UCB – grant/research support (on behalf of Leuven Research and Development), Consultant of: AbbVie, Boehringer Ingelheim, Celgene Corporation, Eli Lilly, Galapagos, Janssen, MSD, Novartis, Pfizer, Samumed and UCB – consultant (on behalf of Leuven Research and Development), Speakers bureau: AbbVie, Boehringer Ingelheim, Celgene Corporation, Eli Lilly, Galapagos, Janssen, MSD, Novartis, Pfizer, Samumed and UCB – speaker (on behalf of Leuven Research and Development), Kurt de Vlam Grant/research support from: Celgene, Eli Lilly, Pfizer Inc, Consultant of: AbbVie, Eli Lilly, Galapagos, Johnson & Johnson, Novartis, Pfizer Inc, UCB, Filip van den Bosch Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB